Women issues in Fanny Fern's work - Štarmanová, Klára (Univerzita Pardubice, 2011)
This paper focuses on the issues of women in the nineteenth century. The aim of this thesis is to analyze selected examples of Fanny Fern's fiction, especially her novel Ruth Hall, with respect to the historical and cultural context. The paper characterizes the Victorian period and its values, attitudes and stereotypes determining women?s subordinate place in society dominated by men. The thesis concentrates especially on the way Fern presents her female protagonist Ruth, describing her in an unconventional manner, portraying a critical view of the accepted nineteenth century interpretation of womanhood.
Ženská problematika v díle Fanny Fern
Keywords: postavení žen; feminismus; Ruth Hall; ekonomická nezávislost; vdovství; mateřství; kritika; position of women; feminism; economic independence; widowhood; motherhood; criticism